Analysis of bulge failure of steel wire-reinforced thermoplastic composite pipe. (June 2023) - Ding, H.; Zhang, A.B.; Li, H.B.; Qi, D.T.; Qi, G.Q.; Ding, N.
Highlights: The failure of this pipe was mainly caused by scratch defects on the inner surface. Because of the poor resin stability near the cracking site compared to its basal resin, the resin matrix on the inner surface appears brittle cracking. The metal wire to be corroded after contacting with the medium, finally forming a bulge on the outer surface. Abstract: A steel wire-reinforced thermoplastic composite pipe (SRTP) was used for water injection connecting line pipe had caused bulge failure of the external surface after 6 years of service. Investigations were performed to identify the most probable causes of the pipe failures. The study was conducted by reviewing the background of the failure, visual physical inspection, test production process analysis, and thermal analysis. The results revealed that the failure of this pipe was mainly caused by scratch defects on the inner surface and the poor resin stability near the cracking site compared to its basal resin. It has scratch defects forming a crack source under the combined action of internal pressure, the resin matrix on the inner surface appears brittle cracking. Subsequently, the medium to be corroded after contacting with the metal wire, losing the pressure bearing effect, and finally forming a bulge on the outer surface under the action of low internal pressure.